A survey on awareness of health staff in the face of nuclear accidents at military hospitals - A Ameryoun; AA Sadeghi; A Aghighi (فصلنامه ابن سینا)
Abstract Background: Increasing development of nuclear technologies and the importance of outbreaking possible accidents based on atomic radiations lead to more readiness and knowledge of health centers, especially military ones. So, the study aimed to measure the awareness of military hospitals medical staffs in exposure to nuclear accidents before any plan to improve future strategies. Materials and methods: The study is descriptive – cross sectional and is performed at 6 selected military hospitals on 120 medical staffs. A questionnaire with 18 questions was used for data collection after confirming the validity and reliability. Results: Totally, %47.2 of participants was female and %52.8 was male. The mean age was 41.1±12.5 years and the average of service duration was 14.5 years. The average score of all groups in three domains was 13.55 of 36. The mean scores obtained by general practitioners, specialists, emergency experts and nuclear technicians, and nurses were 16.1, 14.7, 12.7, and 11.9, respectively. Conclusion: Concerning the point that all groups in three fields could not obtain even the half of complete score, planned retraining courses for current medical staffs seems to be necessary.